(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This paper presents the preparation of PP/CHA melt-blown nonwoven fabric and the studies on its hydrophilic property. The property of polymer materials was investigated at the first place by differential thermal analysis (DSC) and rheology analysis. SEM was used to study the web structure afected by the hot air temperature. Wide-angle X-ray Diffraction (WAXD) was used to study the degree of crystallization of PP/CHA melt-blown nonwovens produced at different hot air temperatures. The hydrophilic property of PP/CHA melt-blown nonwoven fabrics was studied by testing the static water contact angle, the liquid wicking rate and the multiple liquid strikethrough time. The static contact angle test proves that hydrophilic properties were obtained by means of using the Commercial Hydrophilic Additive (CHA), while the addition of the Traditional Hydrophilic Additive (THA) did not. The liquid wicking rate test shows that PP/CHA nonwoven fabric has the highest liquid wicking rate due to its hydrophilic groups transferred to the surface and forming a hydrophilic film. The multiple liquid strikethrough time indicates that the nonwoven fabric treated by THA loses its wettability after 3 insults, while nonwovens containing 5.5% CHA remained hydrophilic even after 12 insults. It can be concluded that PP/CHA melt-blown nonwoven fabrics have durable hydrophilic property.